A robotic/mechatronic mammotome system for minimally invasive breast cancer surgery - Ranjan Kumar Mishra (2008)
This report describes the details of work done based on the novel objective of developing a minimally invasive surgical alternative for breast cancer treatment. The potentiality of the directional vacuum assisted biopsy (Mammotome breast biopsy device from Johnson & Johnson) enabling multiple tissue excision in a single incision has been considered as the surgical modality in the present research work.